TRDMT1 methyltransferase gene knockout attenuates STING-based cell death signaling during self-extracellular RNA-mediated response in drug-induced senescent osteosarcoma cells - Gabriela Betlej; Anna Deręgowska; Maciej Wnuk; Dominika Błoniarz; Tomasz Szmatoła; Katarzyna Klimczak; Jagoda Adamczyk-Grochala; Julia Świętoń; Anna Lewińska (Cellular and Molecular Life Sciences)
Abstract Under stress conditions, endogenous biomolecules such as nucleic acids or proteins can be released from damaged cells and considered as damage-associated molecular patterns (DAMPs) activating innate immune system and context-dependent responses. In the present study, self-extracellular RNA was obtained from dying (RNA D) and senescent (RNA S) cellular models of osteosarcoma (OS), characterized by NGS, and tested against proliferating and non-proliferating (etoposide-indued senescent) OS cells (U-2 OS, SaOS-2, MG-63, 143B). RNA D and RNA S induced apoptosis, nitro-oxidative stress, nucleic acid sensing pathways and cytokine production, and RNA m5C methyltransferase-based responses (TRDMT1 and NSUN2) in proliferating OS cells. In drug-induced senescent OS cells, TRDMT1 gene knockout (KO) prevented STING activation, related proinflammatory response, and cell death. Furthermore, IFN-β binding RNA partners were identified, namely NSUN2, NSUN5, NSUN6, CDKN1A, MYC, and RAD51 transcripts and these interactions were compromised in TRDMT1 KO cells and upon RNA D and RNA S treatment. TRDMT1 KO also resulted in replication stress in OS cells that was potentiated by RNA D and RNA S stimulation and associated with elevated levels of APOBEC3A and APOBEC3G, members of the cytidine deaminase protein family. In conclusion, we showed that TRDMT1 KO restricted STING-based immune and cell death response to RNA D and RNA S in non-proliferating drug resistant OS cells that might have potential therapeutic implications.